Access control using bluetooth / Esmawanie Esa - Esa, Esmawanie (2005)
This thesis project proposes a method of access control using Bluetooth. Currently access control methods require physical contact to a device, such as a swipecard. Bluetooth is a wireless technology that could be used to replace such applications, and provide the convenience of wireless access control. The purpose of this thesis is to demonstrate that such a concept is feasible, by implementing one such application. The application developed in this thesis involves the shutting off of ringing tones of mobile phones that enter a "silent" zone. Such a policy is enforced by a Bluetooth access point situated in this "silent" zone. The access point will send out a "beacon" signal to the mobile phone, via Bluetooth, telling it to shut down its ringing tone. Another focus of this thesis is to ensure that this procedure is secure. Both the mobile phone and access point will have to carry out an authentication procedure, designed in this thesis. With the success of this thesis, such a concept could be extended to other forms of access control applications.